Sexual health education issues (challenges) for adolescent boys in Iran: A qualitative study - Fariba Askari; Khadigeh Mirzaiinajmabadi; Mahmood Saeedy Rezvani; Seyyed Mohsen Asgharinekah (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Sexual health education, especially in adolescents, faces excess challenges in many cultures. Iranian adolescents, especially boys, have many educational needs in the field of sexual health that have not been met due to various obstacles. The main purpose of this qualitative study was to explore the challenges of sexual health education for Iranian adolescent boys. MATERIALS AND METHODS: This qualitative content analysis study was conducted through individual semi-structured in-depth interviews from 45 participants (20 adolescents and 25 key adults). Data were analyzed using inductive conventional content analysis based on the Graneheim and Lundman's approach via MAXQDA software (version 2010) by VERBI GmbH Company, Berlin, Germany. RESULTS: In total, 2 categories and 11 subcategories emerged; including, "extrapersonal barriers to sexual health education for adolescent boys" containing seven subcategories of lack of clear policies, family inadequacy, social barriers, cultural heterogeneity, school inadequacy, cyber threats, and educational process inadequacy concerning adolescent sexual health education as well as "intrapersonal barriers to sexual health education for adolescent boys" comprised four subcategories of uncontrolled emotions of adolescence, adolescent rebellion, information and communication weaknesses, and adolescents' concerns about being judged by others. CONCLUSION: The findings clarify some barriers to sexual health education for adolescent boys. Therefore, it was recommended to develop community-based educational programs to change attitudes of families and society toward addressing the challenges of providing sexual health education to adolescent boys. Moreover, it was suggested to utilize an educational program specific to adolescent boys, tailored to the Iranian culture, using the potential of religion.